1987
DOI: 10.1128/mcb.7.7.2457
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transfected mutant beta-actin genes: alterations of cell morphology and evidence for autoregulation in actin pools.

Abstract: Two different mutant human j-actin genes have been introduced into normal diploid human (KD) fibroblasts and their immortalized derivative cell line, HuT-12, to assess the impact of an abnormal cytoskeletal protein on cellular phenotypes such as morphology, growth characteristics, and properties relating to the neoplastic phenotype. A mutant ,-actin containing a single mutation (Gly-244 --Asp-244) was stable and was incorporated into cytoskeletal stress fibers. Transfected KD cells which expressed the stable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 37 publications
4
61
1
1
Order By: Relevance
“…Alternatively, G-actin could activate or inactivate a regulatory protein which binds to a 5' regulatory element of the actin gene complex [13]. In line with the present study, down regulation of the endogenous actin synthesis was observed in human fibroblasts after transfection and expression of a mutant p-actin gene [36]. In contrast, transfection of mouse myoblasts with human P-actin and y-actin genes and consecutive expression resulted in a transcriptional down regulation of the endogenous actin synthesis in y-actin transfectants but not in p-actin transfectants [37].…”
Section: Discussionsupporting
confidence: 76%
“…Alternatively, G-actin could activate or inactivate a regulatory protein which binds to a 5' regulatory element of the actin gene complex [13]. In line with the present study, down regulation of the endogenous actin synthesis was observed in human fibroblasts after transfection and expression of a mutant p-actin gene [36]. In contrast, transfection of mouse myoblasts with human P-actin and y-actin genes and consecutive expression resulted in a transcriptional down regulation of the endogenous actin synthesis in y-actin transfectants but not in p-actin transfectants [37].…”
Section: Discussionsupporting
confidence: 76%
“…ADP-ribosylated Gteins, appears to be under autoregulatory control on the act i n acts as a F-actin capping protein (12), thereby basis of the equilibrium between the monomeric and the increasing the cellular pool of monomeric G-actin (13). polymeric form (4)(5)(6)(7)(8). Under experimental conditions, In cultured rat hepatocytes, the stabilizing of F-actin by ! )…”
Section: Introductionmentioning
confidence: 99%
“…As a major constituent of the cytoskeleton or myofilaments, it is essential for the maintenance of cell polarity and motility (Bretcher, 1991;Cooper, 1991;Levitt et al, 1987;Pollard and Goldman, 1993), intracellular transport (Kuznetsov et al, 1992), protein synthesis (Hesketh and Pryme, 1991;Negrutskii and Deutscher, 1991;Yang et al, 1990), enzymatic processes (Farwell et al, 1990;Hunt et al, 1990;Knull and Walsh, 1992;Sarndahl et al, 1989), and mRNA localization (Singer, 1992;Sundell and Singer, 1991;Yisraeli et al, 1990). In chicken embryonic fibroblasts and myoblasts, actin mRNA is highly localized at the leading lamellae, quite different from the distribution of mRNAs coding for either vimentin or tubulin (Lawrence and Singer, 1986).…”
mentioning
confidence: 99%
“…As a major constituent of the cytoskeleton or myofilaments, it is essential for the maintenance of cell polarity and motility (Bretcher, 1991;Cooper, 1991;Levitt et al…”
mentioning
confidence: 99%